Вы находитесь на странице: 1из 7

# 4 Linear Equations I & II

Paper 1
1
6. 6 – ––x = x
1. 2h = h + 3 2
2h – h = 3 1
6 = x + ––x
h = 3 2
3
Answer: C 6 = ––x
2
6 × 2 = 3x
2. 3k = 12 – k 3x = 12
3k + k = 12 12
4k = 12 x = –––
3
12 = 4
k = –––
4
= 3 Answer: A

7. –––––– = 5
2
p 5 m – 1 = 5 × 2
–– = ––
3.
2 4 m – 1 = 10
5 m = 10 + 1
p = –– × 2
4 = 11
5
= –– Answer: C
2
Answer: B 2 –– 3
8. ––n = 4
x 2 × 4 = 3 × n
––
4. – 1 = 4 8 = 3n
3
x 8
–– = 4 + 1 n = ––
3 3
x = 5 × 3
= 15 Answer: B
Paper 2
2y
5.
––– + 1 = 3 1. 3x + y = 11......................1
5
x + y = 7........................2
2y
––– = 3 – 1 1 – 2: 2x = 4
5 4
2y = 2 × 5 x = ––
2
10 = 2
y = –––
2
= 5 Substituting x = 2 into 2,
2 + y = 7
Answer: A y = 7 – 2
= 5

## 1 © Penerbitan Pelangi Sdn. Bhd.

Mathematics  SPM  Chapter 4

2. 2m + n = 15......................1
m – n = 3........................2
1 + 2: 3m = 18
18 Paper 1
m = –––
3
= 6 1. x – 2 = 4(1 + 2x)
3
Substituting m = 6 into 1, 3(x – 2) = 4(1 + 2x)
2(6) + n = 15 3x – 6 = 4 + 8x
12 + n = 15 –6 – 4 = 8x – 3x
n = 3 –10 = 5x
x = –2
3. 5h – k = 19..........................1 Answer: A
2h – k = 7............................2
1 – 2: 3h = 12 7y – 2 = 4 – y
2.
12 3
h = –––
3 7y – 2 = 3(4 – y)
= 4 7y – 2 = 12 – 3y
7y + 3y = 12 + 2
Substituting h = 4 into 2,
10y = 14
2(4) – k = 7
8 – k = 7 y = 14
10
8 – 7 = k
k = 1 = 7
5
4. 3a + 2b = 5............................1
3a – b = 11..........................2
p–1 p–3
1 – 2: 3b = – 6 3. – =1
2 3
–6
b = ––– Multiply both sides by 6,
3
= –2 3(p – 1) – 2(p – 3) = 6
3p – 3 – (2p – 6) = 6
Substituting b = –2 into 1, 3p – 3 – 2p + 6 = 6
3a + 2(–2) = 5 p + 3 = 6
3a – 4 = 5 p = 6 – 3
3a = 5 + 4 = 3
9
a = –– Answer: A
3
= 3
4. 4x – 1 = x + 1
5 3
5. 4e + 3f = 18.........................1
3(4x – 1) = 5(x + 1)
e – 3f = 12.........................2
12x – 3 = 5x + 5
1 + 2: 5e = 30
12x – 5x = 5 + 3
30
e = ––– 7x = 8
5
8
= 6 x = ––
7
Substituting e = 6 into 1, Answer: D
4(6) + 3f = 18
24 + 3f = 18
5. 12 – 3(1 – t) = 7t + 2
3f = 18 – 24
12 – (3 – 3t) = 7t + 2
= –6
12 – 3 + 3t = 7t + 2
–6
f = ––– 9 – 2 = 7t – 3t
3
7 = 4t
= –2
7
t = ––
4

## © Penerbitan Pelangi Sdn. Bhd. 2

Mathematics  SPM  Chapter 4

3(p – 1) p 1
6. 2 – = Substituting v = –– into 2,
2 3 2
Multiply both sides by 6, 1
2 –– + k = –3
12 – 9(p – 1) = 2p 2
12 – (9p – 9) = 2p 1 + k = –3
12 – 9p + 9 = 2p k = –3 – 1
21 = 2p + 9p = –4
21 = 11p
21 1
p = ––– 3. –– w – 3h = 5 ......................... 1
11 2
5w + 6h = 14 ....................... 2
Answer: D 1 × 2: w – 6h = 10 ....................... 3
2 + 3: 6w = 24
3 24
7. –– – m = –3(1 – m) w = –––
2 6
3 = 4
–– – m = –3 + 3m
2
3 Substituting w = 4 into 2,
–– + 3 = 3m + m 5(4) + 6h = 14
2
20 + 6h = 14
9
–– = 4m 6h = 14 – 20
2
–6
9 h = –––
m = ––––– 6
2×4
= –1
9
= ––
8
4. 3g – h = 10.................... 1
g + 4h = –14.................. 2
1 × 4: 12g – 4h = 40.................... 3
2 + 3: 13g = 26
Paper 2
g = 2
1. 3m – 4n = 13..................... 1 Substituting g = 2 into 2,
6m + n = –1..................... 2 2 + 4h = –14
2 × 4: 24m + 4n = –4..................... 3 4h = –14 – 2
1 + 3: 27m = 9
9 –16
m = ––– h = ––––
27 4
1 = –4
= —
3
1 5. 4e + 3f = 21.................. 1
Substituting m = –– into 2, e – 6f = 3.................... 2
3
1 2 × 4: 4e – 24f = 12.................. 3
6  –– + n = –1 1 – 3: 3f – (–24f) = 9
3
2 + n = –1 27f = 9
9
n = –1 – 2 f = –––
27
= –3 1
= ––
3
2. 4v – 3k =
14....................... 1
1
2v + k =
–3....................... 2 Substituting f = –– into 2,
3
2 × 3: 6v + 3k =
–9....................... 3 1
1 + 3: 10v =
5 e – 6  –– = 3
3
5
v = ––– e – 2 = 3
10 e = 3 + 2
1
= –– = 5
2

## 3 © Penerbitan Pelangi Sdn. Bhd.

Mathematics  SPM  Chapter 4

1 3. 5m + 4 = 18 – (2 – m)
6. x + 2y = –3.................... 1
4 5m + 4 = 18 – 2 + m
x – 2y = 8...................... 2
5m – m = 18 – 2 – 4
1 × 4: x + 8y = –12.................. 3
4m = 12
2 – 3: –2y – 8y = 8 – (–12)
12
–10y = 20 m = –––
4
y = –2
= 3
Substituting y = –2 into 2,
x – 2(–2) = 8 Answer: D
x + 4 = 8
x = 8 – 4 4. 12 = 2h – 3(2h – 2)
= 4 12 = 2h – (6h – 6)
12 = 2h – 6h + 6
7. m + 4n = 4......................... 1 12
– 6 = – 4h
3 6 = – 4h
––m – n = –5....................... 2 6
4 h = – ––
2 × 4: 3m – 4n =
–20..................... 3 4
1 + 3: 4m =
–16 3
= – ––
–16 2
m = ––––
= –4
Substituting m = –4 into 1, 5. w + 2 = 5 – 2(w – 6)
–4 + 4n = 4 w + 2 = 5 – (2w – 12)
4n = 4 + 4 w + 2 = 5 – 2w + 12
8 w + 2w = 5 + 12 – 2
n = ––
4 3w = 15
= 2 15
w = –––
3
= 5

Paper 1 6. 2x – 3 =
7– 2(x + 1)
2x – 3 =
7– (2x + 2)
1. 8 – 3(v + 2) =
v 2x – 3 =
7– 2x – 2
8 – (3v + 6) =
v 2x + 2x =
7– 2+3
8 – 3v – 6 =
v 4x =8
8 – 6 =
v + 3v 8
4v 2 = x = ––
4
2 = 2
v = ––
4
= ––
2
7. 3(2f – 5) – (3 – 2f) = 2
6f – 15 – 3 + 2f = 2
8f – 18 = 2
2. 14 =
3p – 4(2p – 3) 8f = 2 + 18
14 =
3p – (8p – 12) 20
14 =
3p – 8p + 12 f = –––
8
14 – 12 =
–5p 5
2 =
–5p = ––
2
2
p = – –– Answer: D
5

## © Penerbitan Pelangi Sdn. Bhd. 4

Mathematics  SPM  Chapter 4

## 8. 5(2q – 7) – (3 – 4q) = 4 2k – 1 k+1

14. –––––– = –––––
10q – 35 – 3 + 4q = 4 2 5
14q – 38 = 4 5(2k – 1) = 2(k + 1)
14q = 4 + 38 10k – 5 = 2k + 2
42 10k – 2k = 2 + 5
q = –––
14 8k = 7
= 3 7
k = ––
9. 1 – 2(p + 1) = –5(p – 1)
1 – (2p + 2) = (–5p + 5) Paper 2
1 – 2p – 2 = –5p + 5
–2p + 5p = 5 – 1 + 2 1. 2e – f =
–8.............................. 1
3p = 6 e + 3f =
10.............................. 2
6 1 × 3: 6e – 3f =
–24............................ 3
p = –– 2 + 3: 7e =
–14
3
= 2 –14
e = ––––
7
Answer: C = –2

## 10. 7(2p + 1) – 4(3p + 2) = 0 Substituting e = –2 into 2,

(14p + 7) – (12p + 8) = 0 –2 + 3f = 10
14p + 7 – 12p – 8 = 0 3f = 10 + 2
2p – 1 = 0 12
f = –––
2p = 1 3
= 4
1
p = ––
2
Answer: B 2. a + 2b =
4......................... 1
3a – 4b =
7......................... 2
h+1 3 1 × 2: 2a + 4b =
8......................... 3
––––––
11. = ––
2 5 2 + 3: 5a =
15
5(h + 1) = 3 × 2 15
a = –––
5h + 5 = 6 5
5h = 6 – 5 = 3
1
h = –– Substituting a = 3 into 1,
5
3 + 2b = 4
Answer: C 2b = 4 – 3
1
b = ––
2h + 7 2
––––––
12. = h
5
2h + 7 = 5 × h 1
3. h + –– k = 1........................... 1
7 = 5h – 2h 2
7 = 3h 2h – k =
10......................... 2
7 1 × 2: 2h + k =
2........................... 3
h = –– 2 + 3: 4h =
12
3
h = –––
4
= 3
k
13. 1 – –– = k – 3
2 Substituting h = 3 into 3,
k 2(3) + k = 2
1 + 3 = k + ––
2 6 + k = 2
3k k = 2 – 6
4 = –––
2 = – 4
4 × 2 = 3k
8
k = ––
3

## 5 © Penerbitan Pelangi Sdn. Bhd.

Mathematics  SPM  Chapter 4

2 Substituting f = 4 into 1,
4. k – –– w = 1.......................... 1
3 4 – 2g = 8
3k + w =
9.......................... 2 4 – 8 = 2g
1 × 3: 3k – 2w =
3.......................... 3 2g = – 4
2 – 3: 3w =
6 – 4
6 g = –––
w = –– 2
3 = –2
= 2
Substituting w = 2 into 2, 1
8. e – ––h = 6............................. 1
3k + 2 = 9 4
3k = 9 – 2 3e + h =
11........................... 2
3k = 7 1 × 4: 4e – h =
24........................... 3
7 2 + 3: 7e =
35
k = ––
3 35
e = –––
7
5. 2p + q =
3.......................... 1 = 5
4p – 3q =
11........................ 2 Substituting e = 5 into 2,
1 × 3: 6p + 3q =
9.......................... 3 3(5) + h = 11
2 + 3: 10p =
20 15 + h = 11
20 h = 11 – 15
p = –––
10 = – 4
= 2
Substituting p = 2 into 1, 9. 2x – 3y =
12........................ 1
2(2) + q = 3 4x + y =
10........................ 2
4 + q = 3 2 × 3: 12x + 3y =
30........................ 3
q = 3 – 4 1 + 3: 14x =
42
= –1 42
x = –––
14
6. 5p + 3n =
4......................... 1 = 3
2p – n =
–5....................... 2 Substituting x = 3 into 2,
2 × 3: 6p – 3n =
–15..................... 3 4(3) + y = 10
1 + 3: 11p =
–11 12 + y = 10
–11 y = 10 – 12
p = ––––
11 = –2
= –1
Substituting p = –1 into 1, 10. e – 4w =
16........................ 1
5(–1) + 3n = 4 3e + 2w =
6.......................... 2
–5 + 3n = 4 2 × 2: 6e + 4w =
12........................ 3
3n = 4 + 5 1 + 3: 7e =
28
9 28
n = –– e = –––
3 7
= 3 = 4
Substituting e = 4 into 2,
7. f – 2g =
8........................... 1 3(4) + 2w = 6
3f + 4g =
4........................... 2 12 + 2w = 6
1 × 2: 2f – 4g =
16......................... 3 2w = 6 – 12
2 + 3: 5f =
20 – 6
20 w = –––
f = ––– 2
5 = –3
= 4

## © Penerbitan Pelangi Sdn. Bhd. 6

Mathematics  SPM  Chapter 4

## 11. 2h + 6k = 9............................ 1 Substituting k = 4 into 2,

1 g – 7(4) = –36
––h – 2k = 3............................ 2
3 g – 28 = –36
2 × 3: h – 6k = 9............................ 3 g = –36 + 28
1 + 3: 3h = 18 = –8
18
h = –––
3 15. 7v – 2w =
24........................ 1
= 6 3v – 4w =
26........................ 2
Substituting h = 6 into 1, 1 × 2: 14v – 4w =
48........................ 3
2(6) + 6k = 9 3 – 2: 11v =
22
12 + 6k = 9 22
v = –––
6k = 9 – 12 11
–3 = 2
k = –––
6 Substituting v = 2 into 1,
1 7(2) – 2w = 24
= – ––
2 14 – 2w = 24
–2w = 24 – 14
12. h + 12k = 1....................... 1 10
4h – 3k = 21..................... 2 w = –––
–2
2 × 4: 16h – 12k = 84..................... 3 = –5
1 + 3: 17h = 85
85
h = ––– 16. 3m + 2n =
9.......................... 1
17
= 5 2m – 3n =
19........................ 2
1 × 3: 9m + 6n =
27........................ 3
Substituting h = 5 into 1, 2 × 2: 4m – 6n =
38........................ 4
5 + 12k = 1 3 + 4: 13m =
65
12k = 1 – 5 65
m = –––
– 4 13
k = –––
12 = 5
1
= – –– Substituting m = 5 into 1,
3
3(5) + 2n = 9
1 15 + 2n = 9
13. –– m + n = –4...................... 1 2n = 9 – 15
3
m – 2n = 23...................... 2 –6
n = –––
1 × 3: m + 3n = –12.................... 3 2
2 – 3: –2n – 3n = 23 – (–12) = –3
–5n = 35
35 17. 3t – 4w =
23....................... 1
n = ––– 2t + 3w =
4......................... 2
–5
= –7 1 × 3: 9t – 12w =
69....................... 3
2 × 4: 8t + 12w =
16....................... 4
Substituting n = –7 into 2, 3 + 4: 17t =
85
m – 2(–7) = 23 85
m + 14 = 23 t = –––
17
m = 23 – 14 = 5
= 9
Substituting t = 5 into 2,
1 2(5) + 3w = 4
14. –– g + 3k = 10................... 1 10 + 3w = 4
4
g – 7k = –36................. 2 3w = 4 – 10
1 × 4: g + 12k = 40................... 3 –6
w = –––
3 – 2: 12k – (–7k) = 40 – (–36) 3
19k = 76 = –2
76
k = –––
19
= 4